(untitled) (Journal of the College of Basic Education, 2022)
The effect of concentrations of a suspension of Bacillus thuringiensis israelensis (commercial preparation under the name Antrol) was studied in adults and larvae of the house fly Musca domestica L. by food treatment under laboratory conditions. The results showed that the treatment of adult food with different concentrations led to the occurrence of cumulative deaths dependent on concentration and time, and that the death rates ranged between 77.78-88.89%, respectively, after five days of treatment. The results of food treatment of second instar larvae of the house fly M. domestica with the above concentrations of bacteria recorded cumulative mortality rates depending on the concentration ranged between 53.53-77%, respectively, with the observation of deformities in the dead larvae represented by shrinkage and blackening of their bodies. The treatment of food for larvae showed the concentration of bacteria